Treatment of engineering waste slurries by microbially induced struvite precipitation mechanisms - He, Yuhan; Liu, Shiyu; Shen, Gangqiang; Pan, Muzhi; Cai, Yanyan; Yu, Jin (Frontiers in Bioengineering and Biotechnology, 2023)
With the development of societal, the growth of engineering constructions scale, and the increase of environmental protection requirements, the necessary of engineering waste mud disposal are increasingly prominent. In this study, microbially induced struvite precipitation (MISP) was introduced to treat engineering waste mud. The study mainly focused on (i) the optimal mineralization scheme for MISP, (ii) the feasibility and the effect of reaction parameters on treating engineering waste mud with MISP, (iii) the mechanism of MISP on treating engineering waste mud. The results showed that the waste mud could be well treated with 8.36×10^6 〖cell∙mL〗^(-1) bacterial, 10 mM urea, the 20 mM phosphate buffer, 25 mM MgCl_2 under pH 7. The kaolin suspension could be effectively flocculated. And the flocculation rate could reach about 87.2% under the optimum mineralization conditions. The flocculation effect was mainly affected by the concentrations of reactants and heavy metals and suspension pH. XRD diffraction patterns showed a strong Struvite (MAP) diffraction peak. SEM photos displayed that the crystals were large under the optimal mineralization conditions and showed the shapes of tilted and prismatic shapes at both ends and kaolin particles adhered to the crystals. In a word, this manuscript provides an effective way to treat of engineering waste mud, and the findings should have positive effect in enhancing the soil fertility enhancement and avoiding the secondary pollution.